Exploring chitin metabolite profiles and sensitivity differences in Collembola species exposed to teflubenzuron - Saúl Fernandes; Diana Ilyaskina; Matty P. Berg; Marja H. Lamoree; Pim E.G. Leonards; Cornelis A.M. van Gestel (Ecotoxicology and Environmental Safety)
Effective environmental risk assessments of chemical plant protection products, such as benzoylurea pesticides, are crucial for safeguarding ecosystems. These pesticides, including teflubenzuron, target chitin synthesis in arthropods but also pose risks to non-target soil fauna like Collembola, which play essential roles in decomposition and nutrient cycling. This study combines traditional toxicity tests with a metabolomic approach to examine the interspecies specific sensitivity of three Collembola species — Sinella curviseta, Ceratophysella denticulata, and Folsomia candida — to teflubenzuron. The investigation focused on reproduction, bioaccumulation, and changes in chitin-related metabolites as indicators of pesticide impacts. Results revealed significant interspecies specific variability in sensitivity, with F. candida showing higher susceptibility towards teflubenzuron, possibly due to greater bioaccumulation factors. Metabolomic analysis highlighted distinct patterns in chitin metabolite alterations among the species, correlating with their differential sensitivity. Notably, metabolites like trehalose and glucose, crucial for chitin synthesis, were significantly affected by teflubenzuron within seven days of exposure. Despite high soil concentrations of the pesticide, S. curviseta demonstrated resilience in traditional life-history endpoints, such as reproduction and survival. However, metabolomics indicated a biochemical response to even low internal concentrations of teflubenzuron, underscoring the complexity of their interactions with environmental stressors. This study emphasizes the importance of incorporating metabolomics to understand the differential responses of non-target organisms to pesticides and advocates for species-specific risk assessments in pesticide regulation. The distinct metabolic responses among Collembola species to chitin synthesis inhibitors provide critical insights into their ecological resilience or vulnerability, enhancing our understanding of ecosystem dynamics and the potential ramifications of chemical exposure.